Antrodia cinnamomea exerts an anti-hepatoma effect by targeting PI3K/AKT-mediated cell cycle progression in vitro and in vivo - Yan Zhang; Pin Lv; Junmei Ma; Ning Chen; Huishan Guo; Yan Chen; Xiaoruo Gan; Rong Wang; Xuqiang Liu; Sufang Fan; Bin Cong; Wenyi Kang (Elsevier, 2022)
Antrodia cinnamomea is extensively used as a traditional medicine to prevention and treatment of liver cancer. However, its comprehensive chemical fingerprint is uncertain, and the mechanisms, especially the potential therapeutic target for anti-hepatocellular carcinoma (HCC) are still unclear. Using UPLC‒Q-TOF/MS, 139 chemical components were identified in A. cinnamomea dropping pills (ACDPs). Based on these chemical components, network pharmacology demonstrated that the targets of active components were significantly enriched in the pathways in cancer, which were closely related with cell proliferation regulation. Next, HCC data was downloaded from Gene Expression Omnibus database (GEO). The Cancer Genome Atlas (TCGA) and DisGeNET were analyzed by bioinformatics, and 79 biomarkers were obtained. Furtherly, nine targets of ACDP active components were revealed, and they were significantly enriched in PI3K/AKT and cell cycle signaling pathways. The affinity between these targets and their corresponding active ingredients was predicted by molecular docking. Finally, in vivo and in vitro experiments showed that ACDPs could reduce the activity of PI3K/AKT signaling pathway and downregulate the expression of cell cycle-related proteins, contributing to the decreased growth of liver cancer. Altogether, PI3K/AKT-cell cycle appears as the significant central node in anti-liver cancer of A. Cinnamomea.